The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/la802685m
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in Hydrogen-Passivated and Organically Modified Nanoporous Silicon Surfaces Studied by Polarization Dependent IR Spectroscopy

Abstract: Infrared spectroscopic ellipsometry (IRSE) was applied for characterization of porous silicon (PSi) electrochemically prepared in acidic fluoride solution. When no formation of SiO2 was involved in the preparation, an anisotropic distribution of PSi bonds with the terminating molecules was achieved. On the contrary, oxidation of PSi samples during the preparation led to an isotropic structure. IR spectra obtained from organically functionalized PSi surfaces suggested that the morphology of the organic layer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…It is noticed that the measured tan Ψ data exhibit peak-shapes characteristic of the response of thin films with uniaxial anisotropy when deposited on metallic and semiconducting surfaces. 12,25 Specifically, tan Ψ data obtained from TCC on Au surfaces exhibit two peak-down features while on SiO 2 /Si, the response results in peak-up and peak-down features. This is typical for materials with anisotropic dielectric functions: the peak-up features in tan Ψ spectra from thin anisotropic films deposited on nonmetallic surfaces are due to the electronic transition dipole moments parallel to the surface and peak-down features are due to those perpendicular to the surface.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticed that the measured tan Ψ data exhibit peak-shapes characteristic of the response of thin films with uniaxial anisotropy when deposited on metallic and semiconducting surfaces. 12,25 Specifically, tan Ψ data obtained from TCC on Au surfaces exhibit two peak-down features while on SiO 2 /Si, the response results in peak-up and peak-down features. This is typical for materials with anisotropic dielectric functions: the peak-up features in tan Ψ spectra from thin anisotropic films deposited on nonmetallic surfaces are due to the electronic transition dipole moments parallel to the surface and peak-down features are due to those perpendicular to the surface.…”
Section: ■ Methodsmentioning
confidence: 99%
“…A recent reflectance and transmittance study of thin films of so-called TDBC J-aggregates reported a very substantial peak value ≃10 6 cm –1 of the absorption coefficient. This finding highlights the potential of these materials for applications in optoelectronic devices and calls for more detailed studies of thin-film properties by methods that can detect anisotropy while relaxing the isotropic distribution assumption. A good example of such approach is ellipsometric measurements of nonaggregated copper phtalocyanine thin films, which were found to exhibit uniaxial anisotropy. Moreover, it was reported that even the small difference in the molecular tilt angle can lead to pronounced differences in the anisotropic dielectric response.…”
Section: Introductionmentioning
confidence: 99%
“…2 is an important step in silicon functionalization, most of the reactions summarized in the top part of the figure have already been previously subjected to comprehensive reviews. The analysis of silicon modification schemes involving radicals, 1,14,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] chemomechanical functionalization, 17 and reactions of carefully prepared partially covered silicon surfaces 2,5,15,44,[45][46][47][48][49][50][51] will not be the focus of this review. Instead, we will concentrate on the most recent studies of thermally induced (primarily condensation) reactions of organic compounds with H-terminated silicon surfaces, interactions of metal-organic compounds with the same surfaces, and surface reactivity of ammonia-exposed silicon, prepared according to the last pathway depicted in Fig.…”
Section: I3 Expected General Trends In Surface Reactivitiesmentioning
confidence: 99%
“…Moreover, up to now only one report on methyl-terminated porous Si surfaces using the infrared ellipsometry spectroscopy (IRSE) technique is available. 18 IRSE has been shown to be extremely sensitive and permits an unambiguous identification of monolayer coverage. This paper shows for the first time the vibrational shift of the "umbrella" symmetric deformation mode between CH 3 and CD 3 groups grafted onto H-terminated Si(111) surfaces using the IRSE spectroscopic method.…”
Section: Introductionmentioning
confidence: 99%